PENERAPAN METODE SIX SIGMA PADA PABRIK TEH CIATER PTPN VIII BANDUNG - Camelia Rizki Agrina (Gapenas Publisher, 2023)
Indonesia is among the 5 largest tea exporting countries in the world, the other 5 countries are India, China, Sri Lanka and Kenya. This makes Indonesia must produce quality tea in order to compete with other countries. One of the companies engaged in the plantation business is PT Perkebunan Nusantara VIII (PTPN VIII). PTPN VIII has several tea plantations spread across West Java and Banten areas. One of the tea plantations managed by PTPN VIII is the Ciater Tea Factory. In carrying out its production process, the Ciater Tea Factory produces defective products that are rejected by the head office. This research is aimed at applying the Six Sigma method to the tea production process at the Ciater tea factory to reduce the defect rate of tea products. The research was conducted using the DMAIC method, identified Critical To Quality (CTQ), calculated DPMO and sigma values, outlined the factors causing defects, provided improvement proposals and improved documentation. The results of this study obtained a sigma value of 4.01 with a DPMO value of 6,054.50 and a cost reduction of Rp. 180,074,340 after process improvements. This shows that the Six Sigma method can effectively reduce the level of product defects that occur in the Ciater Tea Factory.